Radiological impacts of the usability of clay and kaolin as raw material in manufacturing of structural building materials in Turkey - Turhan, Şeref (J. Radiol. Prot, 2009)
The aim of the present study is to measure the natural radioactivity due to the presence of radionuclides in clay and kaolin, used widely as raw materials in ceramics, bricks and cement industries, and to assess the possible radiological hazards associated with these raw materials. The activity concentrations of natural radionuclides 226Ra, 232Th and 40K in 50 samples collected from different quarries were measured by means of gamma-ray spectrometry with an HPGe detector. The mean values of the measured activity concentrations of 226Ra, 232Th and 40K for clay samples were found to be 39.3 ± 22.7 Bq kg−1, 49.6±27.9 Bq kg−1 and 569.5±181.0 Bq kg−1, and for kaolin samples 82.0± 37.3 Bq kg−1, 94.8 ± 49.2 Bq kg−1 and 463.6 ± 544.9 Bq kg−1, respectively. These levels are comparable to those appearing in clays of European countries. The radium equivalent activity and the external (gamma) and internal (alpha) hazard indices were calculated to assess the potential radiological hazard. The calculated gamma and alpha indices varied from 0.19 to 1.17 and from 0.04 to 0.47 for clay samples and from 0.36 to 1.75 and from 0.08 to 0.63, respectively. The mean value of the gamma index for the clay samples (0.57±0.24) is slightly above the criterion of 0.5 corresponding to an annual effective dose of 0.3 mSv, while the mean value of the gamma index for the kaolin samples (0.90±0.49) is below the criterion of unity corresponding to an annual effective dose of 1 mSv. The calculated alpha index values for all samples are below the recommended upper level.